Zinc-aluminum-magnesium coated steel plate with excellent degreasing property and manufacturing method thereof

By forming an organic film layer with a thickness of ≥20nm on the surface of the zinc-aluminum-magnesium-coated steel plate, the problem of weak degreasability under severe degreasing conditions is solved, and the continuous integrity of the water film on the steel plate is achieved, and the formation quality of subsequent phosphating crystallization and zirconium-forming film is improved.

CN119899993APending Publication Date: 2025-04-29BAOSHAN IRON & STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311406006.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The zinc-aluminum-magnesium-coated steel plate has weak degreasability under severe alkali degreasing conditions, resulting in discontinuity of water film on the surface of the steel plate, affecting the subsequent formation of phosphating crystallization and zirconium-forming film, thereby weakening the paint film binding force and under-film expansion resistance of the electrophoretic layer.

Method used

On the surface of the zinc-aluminum-magnesium plating layer, an organic film layer with a thickness of ≥20 nm is formed. The film layer is covered with nanotrees in the eutectic structure and has polar functional groups to ensure its hydrophilicity.

Benefits of technology

By forming an organic film layer, the penetration of the anti-rust oil film is isolated, the contact between the plating and oil is eliminated, and the degreasability of the steel plate is improved, so that it can achieve the same degreasing water hanging rate as GI or GA coating under severe degreasing conditions, ensuring the continuous and integrity of the surface water film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899993A_ABST
    Figure CN119899993A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-aluminum-magnesium coated steel plate with excellent degreasing property, which comprises a substrate and a zinc-aluminum-magnesium coating, the surface of the zinc-aluminum-magnesium coating is provided with a hydrophilic organic film layer, the organic film layer covers a nano groove in a eutectic structure of the zinc-aluminum-magnesium coating, and the organic film layer has a polar functional group; the thickness of the organic film layer is larger than or equal to 20 nm. Correspondingly, the invention further discloses a manufacturing method of the zinc-aluminum-magnesium coated steel plate. The zinc-aluminum-magnesium coated steel plate has excellent degreasing property under the harsh alkali degreasing condition, so that the zinc-aluminum-magnesium coated steel plate can be suitable for automobile structural parts, inner plates and outer plates which have high requirements on the surface quality and the formability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate and a manufacturing method thereof, and in particular to a coated steel plate and a manufacturing method thereof. Background Art

[0002] Zinc-aluminum-magnesium coated steel sheet is an upgraded product of hot-dip galvanized steel sheet. By adding a certain amount of Al and Mg to the galvanizing solution, the corrosion resistance is significantly improved, while better formability and good weldability can be obtained. In recent years, zinc-aluminum-magnesium coated steel sheet has been increasingly used in car bodies. It can replace continuous hot-dip galvanizing (GI) car body materials by thinning the zinc layer.

[0003] As one of the four major manufacturing processes of automobiles, painting plays a role in protecting the car body from corrosion and beautifying its appearance. In the painting process, the first process is degreasing, which aims to remove the anti-rust oil on the surface of the steel plate and form a continuous water film on the surface of the steel plate. This process has an important impact on the subsequent phosphating crystallization or zirconization film formation.

[0004] On the one hand, unqualified degreasing will cause discontinuous water film on the surface of the steel plate, which may cause floating dirt to directly adhere to the surface of the steel plate and cause electrophoretic defects. On the other hand, it may cause poor phosphating crystallization and significantly low zirconization film weight, thereby weakening the paint film bonding strength and under-film corrosion resistance of the subsequent electrophoretic layer.

[0005] Based on the current research, the degreasing property of zinc-aluminum-magnesium coated steel sheets is significantly weaker, inferior to the GI and GA coated steel sheets currently commonly used in automobile factories. This indicates that there are oil residues on the surface of the zinc-aluminum-magnesium coating, which may further hinder the subsequent phosphating crystallization or zirconization film formation. After further research, it was found that unqualified degreasing of zinc-aluminum-magnesium coated steel sheets has little effect on phosphating crystallization, but significantly reduces the weight of the zirconization film, which in turn seriously weakens the bonding strength of the electrophoretic layer paint film and the resistance to corrosion under the film. Summary of the invention

[0006] One of the purposes of the present invention is to provide a zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties, which has excellent degreasing properties under severe alkaline degreasing conditions, so that it can be suitable for automotive structural parts and inner and outer panels with high requirements on surface quality and formability.

[0007] In order to achieve the above object, the present invention provides a zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance, which comprises a substrate and a zinc-aluminum-magnesium coating, wherein:

[0008] The surface of the zinc-aluminum-magnesium coating has a hydrophilic organic film layer, the organic film layer covers the nano-grooves in the eutectic structure of the zinc-aluminum-magnesium coating, and the organic film layer has polar functional groups;

[0009] The thickness of the organic film layer is ≥20 nm.

[0010] Through extensive research, the inventors found that under harsh alkaline degreasing conditions (similar to the degreasing conditions of the paint production line in an automobile factory), that is, the degreasing liquid contains anti-rust oil, which consumes a large amount of surfactant, causing the degreasing ability of the degreasing liquid to drop significantly. The degreasing property of zinc-aluminum-magnesium coated steel plates is significantly weaker, inferior to that of GI and GA coated steel plates.

[0011] If the degreasing of zinc-aluminum-magnesium coated steel plates is unqualified, on the one hand, it will cause the water film on the surface of the steel plate to be discontinuous, causing floating dirt to directly adhere to the surface of the steel plate and increase the probability of electrophoretic defects. On the other hand, it will make the weight of the zirconization film significantly lower, which will seriously weaken the bonding strength of the electrophoretic layer paint film and the resistance to under-film corrosion.

[0012] The inventors have found through research that the weak degreasing property of zinc-aluminum-magnesium coated steel sheets is closely related to the multiphase structure of the coating surface. For zinc-aluminum-magnesium coated steel sheets, the zinc-aluminum-magnesium coating surface has: primary zinc phase + binary eutectic structure (Zn / MgZn2) + ternary eutectic structure (Zn / MgZn2 / Al). Among them, the ternary eutectic structure is relatively dense, and tiny nano-scale Al particles are deeply hidden in the nano-scale microscopic grooves of the eutectic. The Al particles and the tiny gaps around them have a strong adsorption effect on oil particles, especially there is a strong van der Waals adsorption force between Al particles and oil particles. When the content of surfactant in the degreasing liquid is low, on the one hand, it is difficult for the surfactant to penetrate into the tiny gaps of the ternary eutectic to capture oil particles. On the other hand, the surfactant that reaches the gap is too small to take away the oil droplets strongly adsorbed by the Al particles, resulting in unqualified degreasing, which is manifested as a discontinuous water film on the plate surface.

[0013] Based on the above research findings, the inventors of this case used a water-based treatment agent to treat the surface of the zinc-aluminum-magnesium coated steel sheet and dried it at high temperature. By forming an organic film layer with a thickness of ≥20nm on the surface of the coating, the dense film can isolate the penetration of the anti-rust oil film on it, avoiding the contact between the coating and the oil, and completely eliminating the possibility of the nano-grooves and Al particles in the eutectic structure adsorbing oil particles, so that the surface oil film is easy to degrease and remove. In addition, the surface of the organic film layer has more polar functional groups, so that it can be well adsorbed with water after degreasing, thereby ensuring that the water film on the surface of the coated steel sheet is continuous and complete. The dual effects significantly improve the degreasing property of the zinc-aluminum-magnesium coated steel sheet, reaching the same level as GI coating or GA coating.

[0014] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the polar functional groups include at least 3 carboxyl functional groups or 2 hydroxyl functional groups.

[0015] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the organic film layer contains acrylic resin or epoxy resin.

[0016] In order to achieve the technical effect of the present invention, the organic film layer must have two properties: one is a high degree of cross-linking to ensure compactness, and the other is a large number of polar functional groups to ensure hydrophilicity. Acrylic resin or epoxy resin can meet the above two requirements at the same time. The acrylic acid, a polymerization monomer of acrylic resin, contains carboxyl groups, which can undergo self-cross-linking reaction to form a dense cross-linked structure. At the same time, the resin contains a large number of carboxyl groups. A considerable number of strongly polar functional groups ensure the hydrophilicity of the film layer. Epoxy resin is condensed from epoxypropane and bisphenol A, has a high degree of cross-linking and has a large number of polar functional groups OH, which ensures good adsorption of water on the surface of the film layer.

[0017] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the thickness of the organic film layer is 20-200nm.

[0018] As mentioned above, when the thickness of the organic film layer is too low, it cannot improve the degreasing performance. However, the inventors have found through experiments and research that when the organic film layer is too high, it will also affect the subsequent welding, phosphating crystallization and zirconization film formation. Based on this, in a preferred embodiment of the present invention, the thickness of the organic film layer is controlled to be 20-200nm.

[0019] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the roughness Ra value of the contact surface between the zinc-aluminum-magnesium coating and the organic film layer is 0.6-1.8 μm.

[0020] In this embodiment, controlling the roughness within the above range is beneficial to further enhance the bonding strength between the organic film layer and the surface of the zinc-aluminum-magnesium coating.

[0021] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 0.8-4.0wt%, Al: 1.0-7.0wt%.

[0022] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 2.0-4.0wt%, Al: 5.0-7.0wt%.

[0023] It can be seen that the present invention is applicable to medium aluminum-zinc-aluminum-magnesium coated steel plates.

[0024] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 0.8-3.5wt%, Al: 1.0-5.0wt%.

[0025] It can be seen that the present invention is also applicable to low-aluminum-zinc-aluminum-magnesium coated steel sheets.

[0026] Furthermore, the zinc-aluminum-magnesium coated steel plate described in the present invention has a degreasing water hanging rate of >95% after degreasing and washing under severe alkaline degreasing conditions, and the severe alkaline degreasing conditions include the alkaline degreasing solution containing 2-4g / L of anti-rust oil.

[0027] Another object of the present invention is to provide a method for manufacturing a zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties. The zinc-aluminum-magnesium coated steel sheet obtained by this method has excellent degreasing properties under severe alkaline degreasing conditions, so that it can be suitable for automotive structural parts and inner and outer panels with high requirements on surface quality and formability.

[0028] Based on the above invention purpose, the present invention also provides a method for manufacturing the zinc-aluminum-magnesium coated steel sheet as described above, which comprises the steps of:

[0029] The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet;

[0030] A water-based treatment agent is coated on the surface of the zinc-aluminum-magnesium coating and heated and cured to form a hydrophilic organic film layer on the surface of the zinc-aluminum-magnesium coating.

[0031] Furthermore, in the manufacturing method of the present invention, the water-based treatment agent contains:

[0032] 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin;

[0033] Nano silicon dioxide 5-15wt%;

[0034] Silane coupling agent 5-10wt%.

[0035] Furthermore, in the manufacturing method of the present invention, the mass percentage ratio of each component of the water-based treatment agent is:

[0036] 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin;

[0037] Nano silicon dioxide 5-15wt%;

[0038] Silane coupling agent 5-10wt%;

[0039] The balance is water and other inevitable impurities.

[0040] In this embodiment, water-soluble acrylic resin or water-soluble epoxy resin is the main film-forming agent. When the content is too low, the number of polar functional groups in the film layer is insufficient, and its hydrophilicity is poor. When the content is too high, the uniformity of the solution formed is insufficient and precipitation is easy to occur. Therefore, it is preferably controlled to be 25-50wt%. Nano-silicon dioxide is an additive, which is mainly used to enhance the compactness of the film layer, prevent moisture from penetrating into the film layer, and improve the corrosion resistance of the coating. In addition, it can improve the viscosity of the surface treatment liquid to a certain extent. When it is too low, the effect is limited, and when it is too high, it is difficult to dissolve completely. Therefore, it is preferably controlled to be 5-15wt%. Silane coupling agent is a film-forming auxiliary agent, which can further improve the cross-linking degree of the film layer and enhance the adhesion between the film layer and the coating. When it is too low, the effect is limited, and when it is too high, the stability of the formulation system is poor. Therefore, it is preferably controlled to be 5-10wt%.

[0041] Furthermore, in the manufacturing method of the present invention, the temperature of heating and curing is 100-140° C., and the heating and curing time is 5-15 s.

[0042] Furthermore, in the manufacturing method of the present invention, an oiling step is also included after the heating and curing step.

[0043] Furthermore, in the oiling step, the amount of oil applied on one side is 300-1800 mg / m 2 .

[0044] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:

[0045] The zinc-aluminum-magnesium coated steel plate with excellent degreasing property described in the present invention forms an organic film layer on the surface of the zinc-aluminum-magnesium coating, thereby isolating the penetration of the anti-rust oil film thereon, avoiding the contact between the coating and the oil, and completely eliminating the possibility of nano-grooves and Al particles in the eutectic structure absorbing oil particles, thereby making the surface oil film easy to degrease and remove.

[0046] The organic film layer of the zinc-aluminum-magnesium coated steel sheet with excellent degreasing property described in the present invention has a large number of polar functional groups on its surface, which enables it to adsorb water well after degreasing and deoiling, thereby ensuring that the water film on the surface of the coated steel sheet is continuous and complete.

[0047] The zinc-aluminum-magnesium coated steel sheet of the present invention has a degreasing water hanging rate of >95% after degreasing and washing under severe alkaline degreasing conditions in which the alkaline degreasing solution contains 2-4g / L of anti-rust oil, and the degreasing property is significantly improved to the same level as GI and GA, so that it can be used for automotive structural parts and inner and outer panels with high requirements on surface quality and formability. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1This is a schematic diagram of the cross-sectional structure of the zinc-aluminum-magnesium coated steel plate with excellent degreasing properties described in the present invention.

[0049] Figure 2 The surface structure of the zinc-aluminum-magnesium coating of Comparative Example 1 is shown.

[0050] Figure 3 This is a local enlarged view of the ternary eutectic structure on the surface of the zinc-aluminum-magnesium coating of comparative example 1. DETAILED DESCRIPTION

[0051] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties and the method for manufacturing the same described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0052] Examples 1-10

[0053] The zinc-aluminum-magnesium coated steel sheets of Examples 1-10 are all prepared by the following steps:

[0054] The substrate is sequentially subjected to hot-dip galvanizing, leveling, surface treatment, oiling and coiling to obtain a zinc-aluminum-magnesium coated steel sheet.

[0055] Figure 1 This is a schematic diagram of the cross-sectional structure of the zinc-aluminum-magnesium coated steel plate with excellent degreasing properties described in the present invention.

[0056] like Figure 1 As shown, the zinc-aluminum-magnesium coated steel sheet of the present invention comprises a substrate 1 and a zinc-aluminum-magnesium coating 2. In addition, the improvement of the present invention is that an organic film layer 3 is formed on the surface of the zinc-aluminum-magnesium coating 2.

[0057] In an embodiment of the present invention, the specific steps of surface treatment are: a water-based treatment agent is coated on the surface of the zinc-aluminum-magnesium coating by a roller coater, and hot air or infrared induction heating is used for curing to form a hydrophilic organic film layer on the surface of the zinc-aluminum-magnesium coating, wherein the organic film layer covers the nano-grooves in the eutectic structure of the zinc-aluminum-magnesium coating, the organic film layer has polar functional groups, and the thickness of the organic film layer is ≥20nm.

[0058] In some embodiments, during heat curing, the plate temperature may be controlled to be 100 to 140° C., and the heating time may be 5 to 15 seconds.

[0059] In some embodiments, the water-based surface treatment agent comprises the following components: 5-15% nano-silicon dioxide, 5-10% silane coupling agent, 25-50% water-soluble acrylic resin or water-soluble epoxy resin, and the rest is water and unavoidable impurities.

[0060] In some embodiments, during the oiling step, the amount of oil applied on one side can be controlled to be 300-1800 mg / m 2 .

[0061] Comparative Examples 1-5

[0062] The zinc-aluminum-magnesium coated steel sheets of Comparative Examples 1-5 were prepared by the following method:

[0063] The substrate was hot-dip coated, leveled, oiled and coiled in sequence to obtain a comparative zinc-aluminum-magnesium coated steel sheet. It can be seen that none of the comparative examples 1-5 was subjected to surface treatment, and therefore the coated surface did not have an organic film layer.

[0064] Table 1 lists the coating chemical element contents of the zinc-aluminum-magnesium coated steel sheets of Examples 1-10 and Comparative Examples 1-5.

[0065] Table 1. (wt%, the balance is Zn and other unavoidable impurities)

[0066] Mg Al Example 1 0.8 1.0 Example 2 1.1 1.6 Example 3 1.4 2.2 Example 4 1.8 2.8 Example 5 2.1 3.4 Example 6 2.4 4.0 Example 7 2.8 4.7 Example 8 3.2 5.4 Example 9 3.6 6.4 Example 10 4.0 7.0 Comparative Example 1 0.8 1.0 Comparative Example 2 1.4 2.2 Comparative Example 3 2.4 4.0 Comparative Example 4 3.2 5.4 Comparative Example 5 4.0 7.0

[0067] Table 2 lists the specific parameters of the surface treatment steps of Examples 1-10.

[0068] Table 2.

[0069]

[0070] Note: In Table 2, Examples 1, 3, 5, 7, 8 and 10 use water-soluble acrylic resins, and the remaining examples use water-soluble epoxy resins.

[0071] In addition, the “type of polar functional group” in Table 2 was measured by infrared spectrometer, and the “number of polar functional groups” was measured by X-ray photoelectron spectroscopy.

[0072] In order to verify the degreasing performance of the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coated steel sheets of the above-mentioned Examples 1-10 and Comparative Examples 1-5 were degreased and then washed with water. The specific degreasing and washing processes are listed in Table 3.

[0073] Table 3. Degreasing and washing process parameters

[0074]

[0075]

[0076] After degreasing and washing, the water hanging rate (i.e. the percentage of water hanging area to the entire board surface area) was measured and the results are shown in Table 4.

[0077] Table 4. Degreasing and water hanging rate

[0078] serial number Degreasing and water hanging rate Example 1 100% Example 2 100% Example 3 100% Example 4 100% Example 5 100% Example 6 100% Example 7 100% Example 8 100% Example 9 100% Example 10 100% Comparative Example 1 10% Comparative Example 2 5% Comparative Example 3 0 Comparative Example 4 10% Comparative Example 5 5%

[0079] As shown in Table 4, under the degreasing process shown in Table 3, the water hanging rate of the zinc-aluminum-magnesium coated steel plates of Examples 1-10 of the present invention is 100%, reaching the degreasing and water hanging rate of GI and GA coated steel plates currently used in automobile factories.

[0080] The degreasing and water hanging rates of the zinc-aluminum-magnesium coated steel sheets of comparative examples 1-5 are only 0-10%, which indicates that the degreasing properties of the zinc-aluminum-magnesium coated steel sheets of comparative examples 1-5 without the organic film layer are significantly weak.

[0081] Figure 2 The surface structure of the zinc-aluminum-magnesium coating of Comparative Example 1 is shown.

[0082] like Figure 2 As shown, the surface structure of the zinc-aluminum-magnesium coating has: primary zinc phase + binary eutectic structure (Zn / MgZn2) + ternary eutectic structure (Zn / MgZn2 / Al).

[0083] Figure 3 This is a local enlarged view of the ternary eutectic structure on the surface of the zinc-aluminum-magnesium coating of comparative example 1 of the present invention.

[0084] like Figure 3 As shown, it can be seen that the ternary eutectic structure is relatively dense, and tiny nano-scale Al particles are deeply hidden in the nano-scale microscopic grooves of the eutectic. There is a strong adsorption effect between the Al particles and the tiny gaps around them on the oil particles, especially the Al particles and the oil particles have a strong van der Waals adsorption force. When the surfactant content in the degreasing liquid is low, on the one hand, it is difficult for the surfactant to penetrate into the tiny gaps of the ternary eutectic to capture the oil particles. On the other hand, the surfactant that reaches the gap is too small to take away the oil droplets strongly adsorbed by the Al particles. Therefore, the degreasing is unqualified, and the macroscopic manifestation is the discontinuity of the water film on the plate surface.

[0085] The present invention forms an organic film layer to cover the nano-grooves in the eutectic structure of the zinc-aluminum-magnesium coating, thereby avoiding the contact between the coating and the oil, and completely eliminating the possibility of the nano-grooves and Al particles in the eutectic structure absorbing oil particles, so that the surface oil film is easy to degrease and remove.

[0086] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0087] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. A zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance, comprising a substrate and a zinc-aluminum-magnesium coating, characterized in that: The surface of the zinc-aluminum-magnesium coating has a hydrophilic organic film layer, the organic film layer covers the nano-grooves in the eutectic structure of the zinc-aluminum-magnesium coating, and the organic film layer has polar functional groups; The thickness of the organic film layer is ≥20 nm.

2. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The polar functional groups include at least 3 carboxyl functional groups or 2 hydroxyl functional groups.

3. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The organic film layer contains acrylic resin or epoxy resin.

4. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The thickness of the organic film layer is 20-200 nm.

5. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The roughness Ra value of the contact surface between the zinc-aluminum-magnesium coating and the organic film layer is 0.6-1.8 μm.

6. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 0.8-4.0wt% and Al: 1.0-7.0wt%.

7. The zinc-aluminum-magnesium coated steel sheet according to claim 6, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 2.0-4.0wt% and Al: 5.0-7.0wt%.

8. The zinc-aluminum-magnesium coated steel sheet according to claim 6, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 0.8-3.5wt% and Al: 1.0-5.0wt%.

9. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: Under the severe alkali degreasing conditions, the degreasing water hanging rate after degreasing and washing is greater than 95%, and the severe alkali degreasing conditions include the alkali degreasing liquid containing 2-4g / L of anti-rust oil.

10. The method for manufacturing a zinc-aluminum-magnesium coated steel sheet according to any one of claims 1 to 9, characterized in that: Includes steps: The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet; A water-based treatment agent is coated on the surface of the zinc-aluminum-magnesium coating and heated and cured to form a hydrophilic organic film layer on the surface of the zinc-aluminum-magnesium coating.

11. The manufacturing method according to claim 10, characterized in that: The water-based treatment agent contains: 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin; Nano silicon dioxide 5-15wt%; Silane coupling agent 5-10wt%.

12. The manufacturing method according to claim 11, characterized in that: The mass percentage ratio of each component of the water-based treatment agent is: 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin; Nano silicon dioxide 5-15wt%; Silane coupling agent 5-10wt%; The balance is water and other inevitable impurities.

13. The manufacturing method according to claim 11, characterized in that: The temperature of heating and curing is 100-140°C, and the heating and curing time is 5-15s.

14. The manufacturing method according to claim 11, characterized in that: The step of oiling is also included after the heat curing step.

15. The manufacturing method according to claim 11, characterized in that: In the oiling step, the amount of oil applied on one side is 300-1800 mg / m 2 .

Citation Information

Patent Citations

  • Galvanized steel sheet and method for manufacturing the same

    CN106062249A

  • Zinc-aluminum-magnesium coated steel plate with excellent adhesive performance and manufacturing method thereof

    CN113122790A

  • Chromium-free passivation solution and method for passivating steel plate by using same

    CN116791073A

  • Inorganic / organic-composite-treated galvanized steel sheet

    CN1575972A

  • Aluminum plate material excellent in moldability and degreasing properties

    JP1993185550A